Estimation of the Poisson’s Ratio of the Rock Mass - Narimani, Samad; Davarpanah, Seyed Motreza; Vásárhelyi, Balázs (Periodica Polytechnica Civil Engineering, 2024)
The value of Poisson’s ratio is a crucial parameter in rock mechanics and engineering for both intact rock and rock mass. Poisson’s ratio has not gotten the attention it merits compared to other essential mechanical characteristics of intact rock and rock mass. Limited relationships exist between rock mass classification systems (such as RMR, RMQR, Q, and GSI) and Poisson’s ratio. This paper provides a comprehensive review of models proposed by various researchers for estimating Poisson’s ratio for rock mass. The different methods are compared, and new general equations are derived. The results indicate that the Poisson’s ratio value of rock mass is inversely proportional to its quality and strength and depends on the Poisson’s ratio value of the intact rock. Specifically, a linear equation is obtained using the RMR or GSI system, showing that the Poisson’s ratio increases as the quality and strength of the rock mass decrease. The Q system has a logarithmic link between the rock mass quality and Poisson’s ratio. It should be noted that the derived equations are applicable only under the assumption of a homogeneous isotropic rock mass.